2009
DOI: 10.14429/dsj.59.1498
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Warhead Among Objects Separation from the Reentry Vehicle in a Clear Environment

Abstract: Separating a reentry vehicle into warhead, main body, and debris is a conventional and efficient means of producing a huge decoy and increasing the kinetic energy of the warhead. This procedure causes the radar to track the main body and debris, which radar cross section are large, and ignore the warhead, is the most important part of the reentry vehicle. The warhead is difficult to identify after separation using standard tracking criteria. This study presents a novel tracking algorithm by integrating input e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Estimation and prediction of ballistic missiles are discussed in [2]. Some recent research work about ballistic missiles and satellite launch vehicles can be found in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Escobal [19] and Nguyen and Dixson [20] have formulated the problem to calculate range of a ballistic missile over the none-rotating oblate spheroid Earth model.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation and prediction of ballistic missiles are discussed in [2]. Some recent research work about ballistic missiles and satellite launch vehicles can be found in [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Escobal [19] and Nguyen and Dixson [20] have formulated the problem to calculate range of a ballistic missile over the none-rotating oblate spheroid Earth model.…”
Section: Introductionmentioning
confidence: 99%